LA PERSONERÍA JURÍDICA: ¿UN TRÁMITE DONDE SE VISLUMBRAN CATEGORÍAS AHISTÓRICAS? UN ANÁLISIS DESDE LA ANTROPOLOGÍA SOCIAL (Glocalism: Journal of Culture, Politics and Innovation, 2024)
In Argentina, there are still certain views on indigenous peoples that have their origins in essentialist arguments built since the formation of the nation state in the 19th century. These are supported by the media, common sense and public policies that directly affect these groups. This paper invites us to question such notions. To do so, we will review the main historical facts and policies that have affected the indigenous populations in Argentina. In order to think about the analytical categories that are still in force about the indigenous populations of the country, at present and in relation to a specific case, the application for legal status in Argentina will be analyzed. This is a procedure to obtain state recognition as an indigenous community, which is usually necessary in order to be able to make different requests. For this purpose, the experience of collaborative work with the Mapuche Kalfulafken community of Carhué, province of Buenos Aires, Argentina, which applied for its legal status in 2019 and which took more than three years to be approved, will be taken up again. The approach of this research was carried out from the perspective of social anthropology and ethnography.
Keywords: anthropology; indigenous peoples; nation state; legal status; Argentina